APOE ε4 Carriers Have a Greater Propensity to Glycation and sRAGE Which Is Further Influenced by RAGE G82S Polymorphism. (2nd November 2019) - Deo, Permal; Dhillon, Varinderpal S; Chua, Ann; Thomas, Philip; Fenech, Michael
Abstract: APOE ε4 allele is an established risk factor for Alzheimer's disease and hypercholesterolemia. However, its association with metabolic and genetic risk factors related to glycation is not clear. We tested the hypothesis that, apart from high plasma cholesterol, APOE ε4 carriers may also have higher advanced glycation end products (AGEs) and total soluble extracellular domain of RAGE (sRAGE) and that these biomarkers may be modified by the common Gly82Ser (G82S) polymorphism (rs2070600) in the RAGE gene. To test this, we measured these biomarkers in 172 healthy cognitively normal individuals, of which 32 were APOE ε4 carriers and 140 noncarriers. APOE ε4 carriers showed higher levels of cholesterol ( p < .001), glyoxal ( p < .001), fluorescent AGEs ( p < .001), N ε -carboxymethyllysine ( p < .001) and sRAGE ( p = .018) when compared to noncarriers. Furthermore, sRAGE was also higher in those that did not carry the A allele of the RAGE gene that codes for serine instead of glycine ( p = .034). Our study indicates that APOE ε4 carriers have a greater propensity to glycation than noncarriers which may further increase their risk for diabetes and dementia. The increased sRAGE levels in APOE ε4 carriers suggests a defensive response against AGEs that may be further influenced by the RAGE G82S polymorphism.